2021
DOI: 10.3390/ph14070654
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for Potential Drug–Drug Interaction of MT921 Using In Vitro Studies and Physiologically–Based Pharmacokinetic Models

Abstract: MT921 is a new injectable drug developed by Medytox Inc. to reduce submental fat. Cholic acid is the active pharmaceutical ingredient, a primary bile acid biosynthesized from cholesterol, endogenously produced by liver in humans and other mammals. Although individuals treated with MT921 could be administered with multiple medications, such as those for hypertension, diabetes, and hyperlipidemia, the pharmacokinetic drug–drug interaction (DDI) has not been investigated yet. Therefore, we studied in vitro agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…To our knowledge, this is the first report on a clinical study of MT921 composed of cholic acid to provide the results such as safety, tolerability and pharmacokinetic profiles along with baseline-adjustments as well as information from the metabolic product, deoxycholic acid, in humans. It has been revealed that the pharmacokinetics of MT921 might not be influenced by co-administered drugs such as amlodipine, simvastatin, and pioglitazone using in vitro and in silico experiments [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report on a clinical study of MT921 composed of cholic acid to provide the results such as safety, tolerability and pharmacokinetic profiles along with baseline-adjustments as well as information from the metabolic product, deoxycholic acid, in humans. It has been revealed that the pharmacokinetics of MT921 might not be influenced by co-administered drugs such as amlodipine, simvastatin, and pioglitazone using in vitro and in silico experiments [ 13 ].…”
Section: Discussionmentioning
confidence: 99%